2021
DOI: 10.1134/s0022093021040177
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Assessment of Effects of Major Mediators of Acute Phase Response (IL-1, TNF-α, IL-6) on Breathing Pattern and Survival Rate in Rats with Acute Progressive Hypoxia

Abstract: A pressing issue of the day is the identification of therapeutic targets to suppress the “cytokine storm” in COVID-19 complicated by acute respiratory distress syndrome (ARDS) with concomitant hypoxemia. However, the key cytokine and its relative contribution to the pathogenesis of ARDS, which leads to high mortality, are unknown. A comparative assessment of the effect of elevated systemic levels of pro-inflammatory cytokines IL-1β, TNF-1α and IL-6 on the respiratory patterns and survival rate in rats was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Similarly, normoxic hypercapnia (15% CO 2 , 20% O 2 , 65%N 2 ) for 24 h did not increase IL1β in BV2 microglial cells in culture (Ding et al, 2018). However, hypercapnia under hypoxic conditions was effective in increasing IL1β both in vivo and in vitro (Ding et al, 2018). Differences with our in vitro results, might be related with the different species (rat vs. mouse), the use of BV2 cell lines instead of primary microglia, distinct stimulation intensity (10% vs. 15% CO 2 ) and duration (2 h vs. 24 h), or perhaps different basal microglial functional states (Paolicelli et al, 2022).…”
Section: Microglia Reactivity and Functional Statesmentioning
confidence: 80%
See 2 more Smart Citations
“…Similarly, normoxic hypercapnia (15% CO 2 , 20% O 2 , 65%N 2 ) for 24 h did not increase IL1β in BV2 microglial cells in culture (Ding et al, 2018). However, hypercapnia under hypoxic conditions was effective in increasing IL1β both in vivo and in vitro (Ding et al, 2018). Differences with our in vitro results, might be related with the different species (rat vs. mouse), the use of BV2 cell lines instead of primary microglia, distinct stimulation intensity (10% vs. 15% CO 2 ) and duration (2 h vs. 24 h), or perhaps different basal microglial functional states (Paolicelli et al, 2022).…”
Section: Microglia Reactivity and Functional Statesmentioning
confidence: 80%
“…By contrast, i. v. IL1β injection increases f R in conscious rats ( Graff and Gozal, 1999 ) and i. p. IL1β injection increases the amplitude of respiratory cycle in anesthetized rats ( Hocker and Huxtable, 2018 ). In urethane-anesthetized normoxic rats, i. v. administration of IL1β increases V T , f R , and V E ( Donina et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL1b, being one of the most studied pleiotropic cytokines, shares similar effects to TNF-α, also referring to the main pro-inflammatory cytokines, which stimulate the production of other cytokines, including IL-6 (Hsieh et al, 2020). To date, it is suggested that IL1b and TNF are involved in neuroimmune interactions in brain regions responsible for central regulation of respiration (Donina et al, 2021). Therefore, it is possible that neuroimmune interactions mediated by IL1b and TNF-α also play a role in peripheral mechanisms of respiratory control that modulate the response to hypoxia and arterial blood oxygen saturation (Donina et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To date, it is suggested that IL1b and TNF are involved in neuroimmune interactions in brain regions responsible for central regulation of respiration (Donina et al, 2021). Therefore, it is possible that neuroimmune interactions mediated by IL1b and TNF-α also play a role in peripheral mechanisms of respiratory control that modulate the response to hypoxia and arterial blood oxygen saturation (Donina et al, 2021). In addition, an association between IL1b levels and moderate to severe neonatal asphyxia is mentioned in the literature (Agustina & Kosim, 2021; Boskabadi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%